Competitive Advantage through Social Entrepreneurship: A Porter’s Diamond Analysis of Empowerment Strategy in Rumah Zakat (Faith-based Social Enterprise) - Mulyaningsih, Hendrati Dwi; Izzati, Nurul; Saraswati, Nindya; Alamsyah, Indra Fajar; Fujitha, Bella (Journal of Social Entrepreneurship Theory and Practice, 2025)
This study explores how Faith-based Social Enterprise’s empowerment strategy, particularly through its Desa Berdaya program which is conducted by Rumah Zakat, generates competitive advantage in the context of social entrepreneurship. Using a qualitative case study design and applying Porter’s Diamond Model as the analytical framework, the research examines four strategic dimensions: factor conditions, demand conditions, related and supporting industries, and firm strategy and structure. Data were collected through in-depth interviews, focus group discussions, and document analysis in Desa Wallagri, one of Rumah Zakat’s flagship empowerment villages. The findings indicate that Rumah Zakat successfully leverages local human and social capital, responds to multidimensional grassroots needs, collaborates with MSMEs and digital platforms, and implements a hybrid governance structure. However, constraints remain, particularly in legal recognition and readiness for internationalization. The study concludes that faith-based social enterprises can achieve scalable impact when they align moral vision with strategic management. Recommendations are offered for practitioners, policymakers, and researchers to support social enterprise ecosystems in achieving sustainable development goals.